Pengetahuan Kearifan Lokal dalam Bercocok Tanam (Nuan-Nuan) Suku Karo di Desa Keling Kecamatan Merdeka Kabupaten Karo - Rosramadhana Rosramadhana; Lidesty Natalia Zipora Sembiring; Nurul Atika; Kartika Sari; Musdiani Silalahi; Meisy Indah Lestari Manalu; Yunda Mustika (Universitas Negeri Medan, 2017)
Local wisdom of planting into a legacy of the ancestral of the ancients. The knowledge traditional in gardening who often ignored when the knowledge of modern came and considered better. However, the public tribes if who inhabit the district independent and ethnicity Karo others in the district Karo still use that knowledge that have inherited by their parents were in to support activities of planting or gardening. Without refused and ignore the knowledge of modern also often in socialitation by local governments to them, the knowledge of local also keep doing and retained. The knowledge of traditional still applied by tribes Karo in the region turns into a background of the estate they can still provide the best to meet the needs of their daily, even also can give contributed to the needs of food in the district curry and in the North Sumatera of the other. Using the research kualitatif and teachnique collecting file thourgh of observation. Interviews are not structure and analysis etnografi as well as the domain. This study give experience the knowledge of the local wisdom in planting of nuan-nuan in the village Keling district Karo free. It turns out the knowledge that they had that is the legacy of their ancestors there are some who still can be used and used of planting that the produce a good product plants